USE OF ACTIVE LEARNING METHODS IN PROFESSIONAL TRAINING OF FUTURE SPECIALISTS - Pashchenko, M.; Chernenko, L. (SWorld-Ger Conference proceedings, 2023)
The article defines the requirements for the use of active learning methods. It is noted that the implementation of role-playing, didactic games in their optimal combination with other methods of professional training in the process of distance learning c